Graduation from poverty: Can a big push program help conflict-affected households? Evidence from Somalia - Hirvonen, Kalle; Karachiwalla, Naureen; Leight, Jessica; Rakshit, Deboleena (International Food Policy Research Institute, 2024)
We are living in one of the most violent periods since the end of the Cold War. Of the 59 active conflicts worldwide, nearly half (28) are unfolding in Africa. Among these, Somalia stands out as a country enduring one of the continent’s longest-running conflicts, stretching back to the 1980s. Nearly 4 million people out of Somalia’s population of 18 million have been forced to flee their homes due to persistent violence and increasingly unstable climate conditions. Many of these internally displaced persons (IDPs) have sought refuge in unplanned, informal settlements in urban areas.